Analysis of vasopressin using capillary electrophoresis with laser-induced fluorescence detector based on competitive immunoassay - Han, KY; Ban, EM; Yoo, YS (ELSEVIER SCIENCE BV, 2003)
A competitive immunoassay based on CE-LIF has been developed for the determination of vasopressin in biological mixtures. Vasopressin participates in the hormonal control of water metabolism and the constriction of arterioles in humans. Thus, detection of vasopressin is important in diagnosing pathological conditions and physiological water metabolism. The peptides were fluorescently tagged with FITC and purified by HPLC. The purified product was then mixed with the cerebrospinal fluid sample followed with the addition of anti-vasopressin antibody. It was possible to separate antibody-bound and free FITC-tagged vasopressin within 10 min by CE-LIF analysis using uncoated fused-silica capillary with high reproducibility. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: NEUROHYPOPHYSEAL HORMONES; ZONE ELECTROPHORESIS; PEPTIDES; CHANNELS; INSULIN; FISH